LGBT in Advertising. How audience’s sexual conservatism influences the attitude towards the ads depicting LGBT characters - Leonidou, Sophia; Voutsa, Maria C. (My University, 2023)
Purpose. In recent years there has been a growing tendency to study the Lesbian, Gay, Bisexual, Transgender, Queer (LGBTQ+) community in advertising (e.g., Li, 2022). Previous studies evaluating X observed inconsistent results on whether LGBT ad portrayals have positive or negative effects on brand attitude and purchase intention. Eisend & Hermann, (2019) conducted a meta-analysis of previous research on the persuasive effects of homosexual portrayals. The outcome showed that the net persuasive effect between homosexual and heterosexual portrayals, as well as between gay and lesbian advertising, did not differ. In another study, Northey et al. (2019) examined how the interaction between gender representation and sexual orientation affect consumer attitudes, reporting disgust as a mediator. Therefore, this study makes a major contribution to research on the effectiveness of LGBT ad portrayals by examining sexual conservatism as a moderator in the relationship between ad portrayal (straight, gay, lesbian, and transgender characters) and ad attitude. Method. A between-subjects single factor (character’s sexual orientation: straight vs. lesbian vs. gay vs. transgender) online experiment was designed for an unknown water brand. Findings. 198 respondents participated in the experiment. A statistically significant ANCOVA effect was observed only for ad irritation (F(3,104) = 4.011, p = .01) and a marginally statistically significant effect for Aad (F(3,104) = 2.167, p = .097). Sexual liberals expressed lower ad irritation than sexual conservatives in ads with gay (p < .001), lesbian (p = .001), and transgender (p = .009) characters. In addition, sexual liberals revealed more positive ad attitude toward gay (p = .001), lesbian, (p = .014), and transgender (p = .024) portrayals than sexual conservatives. In the ad depicting straight characters a non-statistically significant difference was found between sexual conservatives and liberals in perceived irritation and ad attitude. Originality. This empirical investigation bridges the research gap posited in examining the moderating role of sexual conservatism in the way consumers behave towards advertisements depicting LGBT portrayals, and more specifically transgender portrayals.
Keywords: LGBT; ad attitude; sexual conservatism; ad irritation